The Integration of Pancasila Values and Religious Moderation in Strengthening Social Harmony in Indonesia - Umi Ali Fatin Fatin (Universitas Negeri Surabaya, 2025)
Indonesia is known as a pluralistic country with diverse ethnicities, cultures, and religions. In this context, the values of Pancasila play a fundamental role as an ideological foundation for maintaining unity amid diversity. Meanwhile, the concept of religious moderation promotes tolerance and balance in religious life. This article aims to examine the integration of Pancasila values and religious moderation as an effort to build social harmony in Indonesia. The method used is qualitative research with a literature study approach by analyzing 25 scientific journals related to the topic. The results indicate that both concepts are interrelated, where Pancasila serves as the moral and ethical foundation for the practice of religious moderation. Consistent implementation of both can strengthen mutual respect, social solidarity, and national awareness in Indonesia’s multicultural society.